Improving Science Terminology Understanding and Mastery Through Who Am I Intervention Among Grade 7 Students of San Martin National High School: A Thematic Literature Review - Tino, Noah Julie; Paja, Denlee Grace; Samoya, Jackielyn (JPAIR Institutional Research, 2026)
Scientific literacy is a cornerstone of modern education, yet its development is hindered by learners’ limited mastery of discipline-specific vocabulary. In the Philippine context, this challenge is evident among junior high school students, where decoding, spelling, and comprehension difficulties restrict higher-order scientific thinking. This study investigates the effectiveness of the "Who Am I?" intervention in improving Grade 7 learners’ mastery of science terminologies at San Martin National High School. Initial diagnostic results from the Philippine Informal Reading Inventory (Phil-IRI) revealed that 26 out of 52 learners were at the Frustration level, showing severe challenges in reading and spelling scientific vocabulary. These difficulties impeded comprehension and reduced confidence, underscoring the need for targeted interventions aligned with the MATATAG curriculum. A three-month intervention was implemented, integrating clue-based identification, spelling reinforcement, visual scaffolds, peer tutoring, and technology-assisted instruction. Results showed significant improvement, with Mean Percentage Scores rising from 42 percent (Poor Mastery) to 78 percent (Proficient Mastery). A paired t-test (t = 15.62, p = 0.0001) confirmed statistical significance. Qualitative findings revealed enhanced confidence, clearer pronunciation, improved spelling, and greater participation in class discussions. Learners found the intervention "fun" and less intimidating, while teachers observed increased engagement. The study supports multimodal and contextualized vocabulary instruction in science education. By embedding literacy-focused strategies, the "Who Am I?" intervention demonstrates that low-cost, replicable approaches can strengthen foundational skills in resource-constrained classrooms. Findings highlight benefits for learners, teachers, curriculum developers, and policymakers, offering evidence for scalable interventions.